Tunable cyano substituents in D–A conjugated polymers accessed via direct arylation for photocatalytic hydrogen production. Issue 91 (26th October 2022) - Ye, Dong-Nai; Zhang, Yu-Jie; Tan, Zhi-Rong; Xing, Yu-Qin; Chen, Zhengwang; Qiu, Jia-Bin; Liu, Shi-Yong
Abstract : A library of STP-based CP photocatalysts with –CN groups at varied positions were designed and facilely synthesized by an atom- and step-economic one-component direct arylation polymerization for a structure–property–performance correlation study. Abstract : 2-Styrylthiophene-based donor–acceptor linear conjugated polymers with tunable cyano substituents are atom-economically obtained via direct C–H arylation for platinum-free photocatalytic hydrogen production, affording a HER of up to 9.79 mmol h −1 g −1 .